Augmented Reality Implementation as a Product Introduction Development Scheme in Logistics - angga wahyu wibowo (Politeknik Negeri Semarang, 2022)
Industrial evolution in the field of computer technology and multimedia is growing rapidly, especially the sophistication of augmented reality technology which has been used as an introduction medium by various companies. The method in this study uses the waterfall technique. This application is built on a mobile device using Unity 3D software which is implemented in the form of a three-dimensional model for product marketing both in warehouses and places for promotion. This digital marketing strategy supports business people in increasing target market satisfaction. By presenting augmented reality technology through three-dimensional visualization, it is hoped that it can add alternative interactive product introduction media so that consumer needs can be seen clearly through smartphones